2006
DOI: 10.1200/jco.2006.24.18_suppl.16027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary cancer in adults (MPCA)

Abstract: 16027 Background: As a result of the improvement in oncological treatments, MPCA could arise as a more frequent problem in Public Health. The purpose of this retrospective review was to estimate both the incidence and medical features of MPCA pts treated at the Instituto Oncológico Henry Moore (IOHM). Methods: We analyzed 17,100 medical charts from our database since 1987 and identified 378 MPC (2,21%). Then we retrieved data over the last eight years (1997–2005). Those pts with at least two second primary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Multiple primary cancers may be determined by three principal and non-mutually exclusive factors: shared etiologic exposure, familial cancer syndromes or other genetic susceptibility factors, and prior cancer treatment. 10 With the exception of a positive family history – in one series, 32% of multiple primary cancer patients had a family history of oncologic diseases 7 – our patient had none of these factors. Tobacco use is one of the major causes of multiple primary cancers, but it is mostly associated with tumors of the lungs and upper aerodigestive tract, 10 and H. pylori seropositivity does not appear to be associated with lung cancer.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Multiple primary cancers may be determined by three principal and non-mutually exclusive factors: shared etiologic exposure, familial cancer syndromes or other genetic susceptibility factors, and prior cancer treatment. 10 With the exception of a positive family history – in one series, 32% of multiple primary cancer patients had a family history of oncologic diseases 7 – our patient had none of these factors. Tobacco use is one of the major causes of multiple primary cancers, but it is mostly associated with tumors of the lungs and upper aerodigestive tract, 10 and H. pylori seropositivity does not appear to be associated with lung cancer.…”
Section: Discussionmentioning
confidence: 61%
“…While some authors state that synchronous tumors occur within two months of each other, and a metachronous tumor occurs more than two months after the initial cancer diagnosis, 6 others would classify malignancies as synchronous if the interval between their diagnoses is less than or equal to six months, and metachronous when tumors occur more than six months apart. 2 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Inaba et al linked the treatment of primary gastric lymphoma, especially DLBCL, with an increased risk for developing gastric adenocarcinomas [ 7 ]. Moreover, an Argentine study concluded that 32% of MPC patients had a family history of cancer [ 8 ]. Indeed, our patient had also a significant family history of cancer (both father and brother died of malignancies).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported whether or not genetic defects involving the mismatch repair system constituted an important risk factor in patients with MPC [ 7 ]. An Argentine research group found 32% of MPC patients had a family history of oncologic diseases [ 8 ]. In this report, we found only one patient (case 5, accounting for 20%) who carried this genetic tendency.…”
Section: Discussionmentioning
confidence: 99%